PENERAPAN MODEL SAVI DALAM PEMBELAJARAN MENULIS CERPEN PADA SISWA - Chairul Bachri Siregar (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
This research is motivated by shortcomings in writing short stories inparticular students to write short stories opposite of events that never happened.It was influenced by the uses of the learning model. The author provides analternative model of SAVI for use in teaching writing. However, previous authorswill test the SAVI models to determine the level of effectiveness. Based on theresearch background, this study refers to some formulation of the problem,namely: 1) How is the ability of class IX students of SMP Negeri 6 Bahorok inlearning to write short stories before and after the SAVI models applied in theexperimental class; 2) How is the ability of class IX students of SMP Negeri 6Bahorok in learning to write short stories without using SAVI models in thecontrol class; 3) Is there a significant difference between the ability to writepoetry class IX students of SMP Negeri 6 Bahorok in the experimental class in thecontrol class. The purpose of this study is to describe things that are listed in theformulation of the problem.The underlying theory is a theoretical model of SAVI "AcceleratedLearning" presented by Dave Meier and Bobbi DePorter, that goodpembelajaranyang it is learning that involves all aspects of the senses, fun(favored students), student-centered, and can can adapt to the way into the worldof students. This study used a quasi experimental research design with pretestposttestcontrol group. The data of this research is the result of the students writea short story consisting of experimental classes and control classes before andafter treatment. Experimental class using SAVI models, while the control classusing concept maps. The results of this study are significant differences betweenthe experimental class after using SAVI models, compared with the control classusing concept maps. Increased ability graders experiment (using models SAVI) by95%, while the increase in the ability of control class (using concept maps) of68%. This suggests that an increase in the students 'ability to write short stories inthe experimental class is higher than the improvement of students' skills in writingpoetry in the control class.